(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The notion of behavioral economy is considered. Solution of the problem using modern information technologies based on cybernetics is being characterized. The emphasis is on the system approach to solving the problem. There are four stages of this process: construction of the task system; simulation of this system; solution of the problem and, accordingly, the adoption of a management decision based on the results obtained. The emphasis is placed on the meaning of game techniques built on the methodology of simulation, in making managerial decision. As a result, it is noted that the simulation of the problem in a behavioral economy consists of two stages: the characteristics of the research object and the technology of this study.